Root development and drought tolerance of wheat-barley introgression lines - Hoffmann, Borbála; Aranyi, Nikolett Réka; Molnár-Láng, Márta (Acta Biologica Szegediensis, 2011)
Interspecific hybridization makes it possible to transfer useful traits, such as stress tolerance, earliness and various desirable traits from one species into another. Addition, substitution and translocation lines developed from wheat-barley (Triticum aestivum L. x Hordeum vulgare L.) hybrids were analyzed to determine how the added barley chromosomes (or segments) influence agronomy traits in wheat. Experiments were carried out at Georgikon Faculty, Keszthely. First we checked the seeds germinating power and the early development of shoots and roots. The drought-tolerance was tested under rain shelter in the field. The morphological and agronomic traits of the introgression lines were studied. Data were obtained for root-shoot ratio (EC: 30-31), heading time (earliness), plant height, morphology and length of ear, components of grain yield. The use of this genetic material in wheat breeding programs can result in new varieties with better adaptation.